Current annealing to improve drain output performance of β-Ga2O3 field-effect transistor. (November 2021) - Bae, Hagyoul; Lee, Khwang-Sun; Ye, Peide D.; Park, Jun-Young
Highlights: DC output performance of a β -Ga2 O3 field-effect transistor (FET) was boosted by 78%. Heat distribution profile including hot-spots and heat sink was simulated based on 3-D numerical simulator. Substrate engineering using buried oxide (BOX) was suggested to minimize power consumption. Thermal interference for several deviceswas described to confirm the practicality. Abstract: Current annealing, which utilizes high level of drain current during device fabrication, is proposed. A semiconductor device β -Ga2 O3 field-effect transistor is preferred as test vehicle because of its inherently high drain current. With just a few seconds of current annealing, drain output performance can be boosted more than 50% without adding other processes. Both electrical measurements and numerical simulations are performed to investigate the annealing behavior. Especially, proposed substrate engineering to promote thermal isolation enables better power consumption during current annealing.